Analysis Of The Effect Of Product Quality On Consumer Satisfaction At CV. Charis Abadi - Hisan Firdaus; Pramanik, Nuniek Dewi (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the effect of product quality on customer satisfaction at CV Charis Abadi, a custom furniture company in Bandung. Product quality is measured through three main indicators: product durability, aesthetics, and conformity to specifications, while customer satisfaction is measured through satisfaction levels, repeat orders, and recommendations to others. The method used is descriptive quantitative with data collected through questionnaires from 33 customers. The results of the analysis indicate a very strong positive and significant relationship between product quality and customer satisfaction (r = 0.881, p < 0.05). Simple linear regression reveals that product quality contributes 77.7% to the variation in customer satisfaction. This means that the better the product quality perceived by customers, the higher their level of satisfaction. These findings emphasize the importance of improving product quality, especially in aspects of durability, aesthetics, and conformity to specifications, as a key strategy to maintain customer loyalty and encourage repeat purchases. This study also provides recommendations for companies to continue innovating in product design and quality to meet evolving market needs and expectations.